Justiça, política e formação na república platônica : a paidéia enquanto caminho para a virtude - Santa, Fernando Dala (2013)
The present study aims to investigate the concept of justice in Plato's Republic, in connection with the concepts of education and virtue, and is supported in a posture analytical reconstructive of hermeneutic nature. We are trying to understand Plato's proposals from the social and intellectual environment that forged, keeping highlighted the concepts with which the author had access, so that we could follow the construction of its argument, abstaining from a reckless judgment external. The Platonic philosophy reveals itself closely linked to political issues, reflecting a determinant in its concern with the educational aspects. The political educational platonic project settles having as one of its fundamental assumptions the construction of an ideal State, based on the functional specialization of each of its members. Justice, initially investigated in the social, configures itself therefore in harmonious hierarchy among the classes that constitute the State (craftsmen, warriors and rulers) and at the individual level is revealed by submission of lower elements (irascible and concupiscent) to rational portion of the soul. However, the plausibility of the proposal of an ideal city was subject to the rule of a government of philosophers. Plato establishes the nature of authentic philosopher, defining it as the only one able to perceive the continuity of the intelligible reality in the chaotic ferment of the sensible world, and therefore able to rule the City, supported by absolute precepts. In his pedagogical program offers a thorough and careful philosophical and moral education for those who become rulers. Through the images of the Sun and the divided line, which are presented at the end of Book VI, and the allegory of the cave, which opens the Book VII, Plato describes allegorically the path to be trodden by the philosopher to the contemplation of the Well, and the full realization its philosophical nature. In the remainder of Book VII, Plato establishes the curriculum that the philosopher would be submitted, composed of mathematical disciplines: arithmetic, geometry, astronomy and harmony, which would form a unit of introductory character, disentangling the spirit of all sensible perception, and preparing to the contact with the dialectic, only science can come to the knowledge of the Well. Plato contributed immensely to the development of the educational problem from its objective to form the true public man, that would able to rule wisely and foster justice in the City, becoming thus also the educator. In these terms, based on the study about the educational principles underlying the construction of the ideal City, with the backdrop of the search for the essence of justice, the reading of the Republic has made possible the establishment of numerous questions with regard to current conceptions of state and individual and mainly on educational paradigms with which we live